Cell-bound complement activation products in systemic lupus erythematosus: comparison with anti-double-stranded DNA and standard complement measurements. Issue 1 (1st October 2014) - Putterman, Chaim; Furie, Richard; Ramsey-Goldman, Rosalind; Askanase, Anca; Buyon, Jill; Kalunian, Kenneth; Chatham, W Winn; Massarotti, Elena; Kirou, Kyriakos; Jordan, Nicole; Blanco, Irene; Weinstein, Arthur; et al.
Abstract : Objective: To compare the performance characteristics of cell-bound complement (C4d) activation products (CBCAPS) on erythrocyte (EC4d) and B cells (BC4d) with antibodies to double-stranded DNA (anti-dsDNA) and complement C3 and C4 in systemic lupus erythematosus (SLE). Methods: The study enrolled 794 subjects consisting of 304 SLE and a control group consisting of 285 patients with other rheumatic diseases and 205 normal individuals. Anti-dsDNA and other autoantibodies were measured using solid-phase immunoassays while EC4d and BC4d were determined using flow cytometry. Complement proteins were determined using immunoturbidimetry. Disease activity in SLE was determined using a non-serological Systemic Lupus Erythematosus Disease Activity Index SELENA Modification. A two-tiered methodology combining CBCAPS with autoantibodies to cellular and citrullinated antigens was also developed. Statistical analyses used area under receiver operating characteristic curves and calculations of area under the curve (AUC), sensitivity and specificity. Results: AUC for EC4d (0.82±0.02) and BC4d (0.84±0.02) was higher than those yielded by C3 (0.73±0.02) and C4 (0.72±0.02) (p<0.01). AUC for CBCAPS was also higher than the AUC yielded by anti-dsDNA (0.79±0.02), but significance was only achieved for BC4d (p<0.01). The combination of EC4d and BC4d in multivariate testing methodology with anti-dsDNA and autoantibodies to cellular and citrullinated antigens yielded 80% sensitivity for SLE and specificity ranging from 70% (Sjogren's syndrome) to 92% (rheumatoid arthritis) (98% vs. normal). A higher proportion of patients with SLE with higher levels of disease activity tested positive for elevated CBCAPS, reduced complement and anti-dsDNA (p<0.03). Conclusions: CBCAPS have higher sensitivity than standard complement and anti-dsDNA measurements, and may help with the differential diagnosis of SLE in combination with other autoantibodies.